Do economic and cultural differences influence family businesses? Comparative study from Czechia and Pakistan - Marie Mikušová; Václav Friedrich; Muhammad Kamal Subhani (Future Business Journal)
Abstract The paper presents the results of strategies and objectives research on family entrepreneurship in two very different countries. Based on study strategies of sustainability, competitiveness, growth, and human resources care were identified. In addition, financial and non-financial objectives were defined, which included family beliefs, family and business interaction, business and community interaction, and succession. A research question has been formulated: do the strategies and key objectives of family business owners in the Czech Republic and Pakistan differ? About 400 responses from family business owners in each country were statistically evaluated. The dependence of strategies and objectives on the generations of owners and their education, control bodies, managers, age and size of the business, and the industry in which it operates were examined. The research results show that despite major economic, cultural and historical differences between the two countries, no significant differences were defined in used strategies and key objectives. This advancing cross-cultural family business research reveals universal characteristics of family business strategy which unite entrepreneurial families across different countries, and provide valuable insights that can guide the development of specialized programs and resources.